Effects of Eimeria maxima and Clostridium perfringens infections on cecal microbial composition and the possible correlation with body weight gain in broiler chickens. (October 2020) - Lu, Mingmin; Li, Robert W.; Zhao, Hongyan; Yan, Xianghe; Lillehoj, Hyun S.; Sun, Zhifeng; Oh, SungTak; Wang, Yueying; Li, Charles
Abstract: With the voluntary and regulatory withdrawal of antibiotic growth promoters from animal feed, coccidiosis and necrotic enteritis (NE) emerge as the top two enteric poultry infectious diseases responsible for major economic loss worldwide. The objective of this study was to investigate the correlation between the cecal microbiota compositions with the growth trait after coccidiosis and NE. In this study, the effects of Eimeria maxima and/or Clostridium perfringens infections on the microbial composition and potential correlation with the body weight gain were investigated in broiler chickens using 16S rRNA gene sequencing. E. maxima and C. perfringens coinfection successfully induced NE with its typical gut lesions and significant reductions in the percentage of relative body weight gain (RBWG%). The NE challenge model did not affect cecal microbial diversity, but influenced the cecal microbial composition. KEGG enzymes in microbiota were significantly altered in abundance following dual infections. Furthermore, significant correlations between cecal microbiota modules and RBWG% were identified in the sham control, E. maxima or C. perfringens infected groups. Understanding of host-microbiota interaction in NE would enhance the development of antibiotics-independent strategies to reduce the harmful effect of NE on the gut microbiota structure, and improve the gut health and poultry production. Highlights: E. maxima and C. perfringens coinfection induced NE with a reduction in RBWG% and increased gut lesion in chickens. Necrotic enteritis altered the cecal microbial composition, and KEGG enzymes of functions. Significant correlation was observed between cecal microbial network modules and RBWG% in non-infected and infected chickens.